The role of spirituality in the treatment of depression: a preliminary result of a qualitative study - Md Rosli, Ahmad Nabil (2019)
Introduction: The conventional approach to the treatment of depression focuses on the pharmacological and psychological treatments. In addition to that, spirituality plays a major role in the preservation of human psychological health, which leads to its application in the prevention, treatment, and rehabilitation of patients with psychological disorders such as, major depressive disorder. Despite this, research on spirituality among Muslims in relation to depression is comparably scant. The objective of this study is to explore the role of spirituality in the treatment of depression among Muslim patients.